THE ANTIBACTERIAL EFFECT OF ROSEMARY (ROSMARINUS OFFICINALIS L.) ON ENTEROCOCCUS FAECALIS BACTERIA AS AN ALTERNATIVE FOR ROOT CANAL IRRIGATION - Aryanto, Mirza; Alawiyah, Tuti; Firdaus, Ihsan (International Journal of Research -GRANTHAALAYAH, 2023)
Background: Root canal treatment is one of the endodontic treatments to preserve teeth with bacterially infected pulp tissue. Root canal irrigation is one of the most important processes to eliminate bacteria in root canals. In the root canals of teeth with failed endodontic treatment, Enterococcus Faecalis bacteria were found, so that alternative irrigation materials were needed that were more effective. Purpose: The aim of this study was to explain the effect of the antibacterial power of rosemary (Rosmarinus officinalis L.) on Enterococcus faecalis bacteria. Methods: The samples tested were 24 in the form of Enterococcus faecalis bacteria culture in BHI agar media in petri dishes. This research uses the well method. Each 1 petri dish was divided into 4 wells and each was given rosemary extract (Rosmarinus officinalis L.) at 5% and 10% concentrations, as well as a positive control (NaOCl 2.5%). Bacteria were grown and incubated, then diluted with 0.5 McFarland standard. (1.5X108 bacteria permilliliter). Results: The average inhibitory power of Enterococcus faecalis in rosemary (Rosmarinus officinalis L.) extract at 5% concentration was 16.7 mm and at 10% concentration was 18.8 mm, while in 2.5% NaOCl solution it was 8 mm. The hypothesis test has a value of p = 0.000 (p < 0.05). Conclusion: Rosemary extract (Rosmarinus officinalis L.) has a more effective inhibition of Enterococcus faecalis bacteria.